IN-VITRO INDUCTION OF GRAPEVINE (Vitis Vinifera L.) SHOOTS USING 2-iP - Dwiyani, Rindang (International Journal of Biosciences and Biotechnology; Vol 4 No 1 (2016), 2016)
The research concerning induction of grapevine shoots grown in vitro have been conducted during period of May to July 2016 at The Laboratory of Plant Tissue Culture, Faculty of Agriculture, Udayana University. The objective of the research was to investigate the most appropriate explant position and the optimal concentration of 2-iP in stimulating of grapevine shoot in vitro. Nodal segment from grapevine plant grown in the green house was used as planting material. The experiment was laid out in the factorial design, with two factors. The first factor was the position of explant (lay-down and up-right position) and the second factor was concentration of 2-iP ( i.e. 0, 3, 6, 9, 12 ppm). Each combination was replicated ten times. The results showed that the treatment of 6 ppm 2-iP with up-right explant position was the most appropriate condition in stimulating growth of grapevine shoot. With up-right position of explant, the percentage of shoot producing-explants at 10 weeks after planting was 100% at the treatment of 6 ppm 2-iP, compared to 4%, 12%, 40%,and 40% at the treatment of 0 , 3, 9 and 12 ppm 2-iP respectively. The average number of shoot per explant was 5.5 for 6 ppm-treatment, while it was less than 3 for other treatments.
Keywords: grapevine shoots; induction; 2-iP; explant position